Relationship Between Knowledge and Attitudes of Adolescents with Personal Hygiene during Menstruation - Ika Putri Damayanti (Institute Of Computer Science (IOCS), 2021)
Female reproductive organs are very sensitive and require special care, especially during menstruation, so that if you don't change sanitary napkins often it can cause allergies and infections. Maintaining cleanliness during menstruation can avoid several reproductive organ problems. The initial survey conducted by researchers from 25 students found only 20% who already knew how to protect their reproductive organs during menstruation, the rest did not know about it. The purpose of this study was to determine the relationship between knowledge and attitudes of adolescents with personal hygiene measures during menstruation. Junior high school. This study used a type of analytic study with a cross sectional design using primary data and distributing questionnaires as a measuring tool to 84 respondents. The population in this study were all adolescents who had menstruation. The sampling technique used in sampling is total sampling. The results of the study, most of the respondents had low knowledge as many as 55 people (65.5%), and most respondents also had low attitudes as many as 54 people (64.3%), and some respondents who did not perform hygienic actions during menstruation were 55 people ( 65.5%). The results of the chi square test of adolescent knowledge and attitudes with hygienin action during menstruation with p value 0.03 and 0.04. The conclusion of this study is that there is a significant relationship between knowledge and hygienic action during menstruation with OR 3.13 (95% CI: 1.21- 8.09) and there is a significant relationship between attitude and hygienic action during menstruation with OR 2.85. (95% CI: 1, 11- 7,31). This research suggestion is expected for the next researcher to conduct research on all adolescents in the school with different types of research and add variables.